Determining the academic & professional profile of accountancy graduates required by employers. - Lee, Meng Hye. (2008)
This project is (1) to investigate the types of industries accounting graduates are employed in in order to assess the relevancy of their education and training; (2)To obtain feedback from accounting graduates on the accountancy programme as a necessary input to curricula review and planning; (3) To assess the views of employers on the professionalism of accounting graduates and the quality of their training.